Information access pattern among the students in Sree Sevugan Annamalai College, Devakottai, Sivagangai district - Murugesapandian2*, K. Senkodi1, N. (International Multidisciplinary Research Journal, 2011)
This study examine the students needs the information and their expectations towards academic and research purpose to visit the library in Sevugan Annamalai College Devakottai, it is a Government aided college and it has been affiliated by the Alagappa University, Karaikudi. This study shows that UG in Computer Science 15.65 percent of users, it followed by UG in English, Zoology and commerce secured 14.78 percent. Under graduate in Commerce and PG in Tamil are hold third level with 13.97 percent. Besides this analysis brings that 40 percent, next 27.82 percent of users visit the library in once in a week, the users visit the library once in a fortnight is 20.86 percent is observed from the study.